(3aJhi aj eUWdM GdMOjK hGdLhGH YdjgGs - (3YHO GdYXje Hf YHO Gdbhj Hf YHO Gddg, CHh eMeO, Rcj GdOjf GdefPQj ,J (B656 (3g` s
(3ChdgG (B:s
(3eGJbhd GdSGOI GdYdeGA hGdCFeI GdaVdG ai gPg GdYHGQGJ GdJi jYHQ HgG CFeI GdMOjK Yf GdQhGg s
(3BNQgG (B:s
(3hddCFeI ai Pdc CLhHI hef bGd gh GdMOjK GdeSfO GdPi jJUdd SfOg Hfbd GdYOd GdVGHW Yf GdYOd GdVGHW hGddg YR hLd CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B30s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCSJGP (B- (3YHO GdeMSf Hf MeO GdYHGO s
Keywords: (3GdMOjK h GdeUWdMs